The Implementation of English for Biology Based on CLIL Student Handbook to Improve English Proficiency of Prospective Student Biology Teacher - A Wahab Jufri; Bachtiar Imam; Aulia Dwi Amalina Wahab; Andra Ade Riyanto (Postgraduate, University of Mataram, 2023)
The ability to communicate using English is an important pillar in establishing international cooperation in the era of Society 5,0. The Faculty of Teacher Training and Education (FKIP) serves as one of the faculty that must facilitate prospective educators. This study aims to examine the contribution of the implementation of English for Biology: Student Handbook through a Content Language Integrated Learning (CLIL)-based learning approach to improve the English proficiency of prospective teacher students in the Biology Education study program, FKIP. The research was carried out with a quasi-experimental approach (quasi-experimental research) with a multiple-group pretest-posttest pattern. The test subjects and the unit of analysis are all second-semester students who take English for Biology lectures at the Biology Education Study Program, FKIP in the 2021/2022 academic year with a total of 6 classes (A, B, C, D, E, and F). The results of the analysis show that there is an increase in students' English proficiency which is in the quite effective category with the acquisition of N-gain scores for classes A, B, C, D, E, and F of 68, 58, 60, 62, 58, and 61. The average value The average N-gain of the English language proficiency of biology education students is 68 with a fairly effective category. Therefore, the use of English for Biology: Student Handbook through a CLIL-based learning approach is quite effective in increasing the English proficiency of prospective educators in the Biology Education Study Program, FKIP, University of Mataram.